Senior high school students’ attitudes towards intercultural insertion into the ELT: Yogyakarta context - Ragil Safitri; Sugirin Sugirin (Universitas Islam Sultan Agung, 2019)
Experts in English Language Teaching often consider culture as the fifth skill in foreign language learning as cultural literacy is a must in 21st-century learning. Thus, this study is to investigate students’ interest in the insertion of Big ‘C’ and little ‘c’ themes from different countries into the English classroom. In this study, the researcher distributed a questionnaire to 58 students in a senior high school in Yogyakarta. The study indicated that the respondents’ preferences were mostly about local culture (Yogyakarta and Indonesian culture), followed by target culture (culture of English-speaking countries) and international culture. In accordance with the cultural themes, they showed a relatively higher preference toward Big ‘C’ over the little ‘c’ culture. Concerning Indonesian culture, the students were excited in learning about art/literature, history, and food while for Yogyakarta culture includes history, foods, and lifestyles. Meanwhile, for target culture (Britain, America, and Australia), the students were eager to learn about lifestyles and foods. The last, for international culture, the cultural themes of lifestyles and music/sports were preferred by the students.